The Pattern of Motorcyclists' Death Due to Accidents and a Three-year Forecast in East Azerbaijan Province, Iran - Ali Jafari-Khounigh; Mahdi Rezaei; Bahram Samadirad; Mina Golestani; Kavous Shahsavarinia; Alireza Razzaghi; Sajjad Ahmadi; Homayoun Sadeghi-Bazargani (Journal of Biostatistics and Epidemiology, 2023)
Introduction: In low- and middle-income countries, a large proportion of road users include pedestrians, cyclists, and motorcyclists, and nearly half of road traffic fatalities occur among motorcyclists. This study aimed to examine the pattern of motorcyclists' death due to accidents in East Azerbaijan, Iran between 2006 and 2021 and present a forecast.